Key factors in the use of Agricultural Extension Services by women farmers in Babati District, Tanzania : the role of societal gender norms - McCormack, Caitlin (SLU/Dept. of Urban and Rural Development, 2018)
Agricultural Extension Services (AES) – defined here as a system of services providing advice, information and training to farmers – are critical for enhancing agricultural productivity and development in Tanzania. Women farmers often face particular constraints to using AES, and consequently have lower levels of access on average than their male counterparts. The constraints women farmers face comprise a range of practical, institutional and norm-based factors. Improving women farmers’ access to and use of AES requires identifying and understanding these constraints and exploring how AES can be designed and delivered to overcome them. In this thesis, I explore women (and men) farmers’ access to and use of AES in two villages in Babati District, Tanzania and identify the critical factors affecting this, with a particular focus on the role of societal gender norms. I also investigate if and how gender is considered within current AES services and explore perceptions of AES practitioners about women farmers as users of AES. Finally, I consider opportunities for (women) farmers to shape AES and how AES may be delivered to better meet their needs. The study is based on empirical data collected during six weeks of fieldwork in Tanzania in March and April 2017. Findings are from group interviews, in-depth individual interviews and observations. The thesis is informed by a liberal feminist perspective and I draw on theory around social norms and institutions, gender norms and relations, and knowledge systems to explore my empirical findings. I find that women farmers’ AES needs and preferences often differ from men farmers’ and that there are multiple factors that affect their willingness and ability to use AES. I argue that many, if not most, of these factors are rooted in societal gender norms. Critically, I also find that current measures within AES to target women farmers do not comprehensively address gender norms and there is an apparent lack of gender capacity amongst institutions and staff involved in providing AES. I conclude that in order to effectively deliver to women farmers and contribute to agricultural development, AES should involve efforts to address the multifaceted ways in which societal gender norms affect AES use and delivery.